If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(m-3)=0
We simplify the equation to the form, which is simple to understand
2(m-3)=0
Reorder the terms in parentheses
+(+2m-6)=0
Remove unnecessary parentheses
+2m-6=0
We move all terms containing m to the left and all other terms to the right.
+2m=0+6
We simplify left and right side of the equation.
+2m=+6
We divide both sides of the equation by 2 to get m.
m=3
| 0.6(n+1)=2.4(n-11) | | -1.6-0.9w=11.6+2.4w | | 4x-3=-10-2x-1 | | 12x^2-54x-108=0 | | 7x+10=2x-15 | | 33f=315 | | x^2+4x=28 | | 5+.15m=16.25 | | 2-18y-6=-7+3+10y | | 5x-5=3x-3 | | 6x-5=27 | | B-19=29 | | 12x^2-90x-48=0 | | 3x-4-6x+10+9x= | | 15d=90 | | y-3(4-2y)=6(y+1) | | 9x-10=-3+2x+7 | | 4=w-10 | | c+88=155 | | 5x+10+5x+10=90 | | b-21=63 | | 6(6v+6)-5=6v | | 3-7x=-9-4x+3 | | 9x^2-5=1 | | 4x-4=x+11 | | -2m=45+7m | | a+14=26 | | 2x+3y=72 | | 15=9+3x | | 18x^2+5x-3=0 | | -6.6-6x-3.7-4x=-9x+6.2 | | 6x-3(y-1)=4x+8 |